PENGARUH PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI KALIMANTAN TENGAH - Irawan Irawan; Puput Iswandyah Raysharie, Amalia, Ayu Nabila, Deby Wulandari, Pera Yunika, Puput Aprilia, Safira Ri (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2023)
The aim of this research is to ascertain the relationship between Central Kalimantan Province's poverty rate and economic growth from 1999 to 2022. This study employs a literature study research methodology, gathering data from books, journals, and other sources. The data was collected from BPS Central Kalimantan's official website. The study's findings demonstrate that poverty in Central Kalimantan is significantly impacted negatively by economic expansion in the region.